Electrochemical oxidation of ascorbic acid mediated by Bi2O3 microparticles modified glassy carbon electrode. - Mohammed Zidan,; Tan, Wee Tee; Abdullah, Abdul Halim; Zainal, Zulkarnain; Goh, Joo Kheng (Electrochemical Science Group, 2011)
Bismuth oxide (Bi2O3) modified glassy carbon electrode (GCE) was fabricated by mechanical attachment. Electrochemical performance of microparticles of Bi2O3/GCE shows excellent electrooxidation of ascorbic acid (AA) in 0.1M KH2PO4 using cyclic voltammetry. The effect of Bi2O3/GCE is evident by the observation of high peak oxidation current of AA, showing an increase of 2 folds as compared to bare GCE. The detection limit of this modified electrode was found to be 8.1 × 10-6M. Hydrodynamic method (RDE) was used to determine the diffusion coefficient and rate constant of AA with values of 5.4 × 10-6 cm2s-1 and 2.7x10-3 cms-1 for unmodified electrode, while the values of 6.2x10-6 cm2s-1 and 2.3x10-3 cms-1 for GCE modified with Bi2O3, respectively.